Shaaf jack light enterprise / Azwa Nadia Mat Asri...[et al.] - Mat Asri, Azwa Nadia; Abu Talib, Nurul Atiqah; Jamil, Nor Hasanah Hayati; Rosli, Elly Syahira; Mohd Omar, Earma Nur Farqah (2014)
Vision: The SHAAF Jacklight Enterprise vision is to inspire its employess to be the best they can be.We will engage in sustainable practices and anticipate the needs customer.We will maximize return to stockholder while still maintaining quality in our products and to be one of the biggest names in industry food in our country. Company Background: Our business name is SHAAF Jacklight Enterprise. "SHAAf" means that combine our group member names. The idea for the business name is created by the partners. Products: This jacket supplied to other shop and individual. This jacket helps people increase their safety in their life. This jacket also multipurpose that can easier the user who buy it. Markets: 'Market target of our products is located at Perlis, Kedah, Pulau Pinang and Perak. In Kedah, we distribute our product at Kuala Nerang, Pendang, Jitra and Bagan Serai district while in Perak, we target our market at whole area. We choose these areas because we believe that our product will have higher demand. Distribution Channels: We have distributed our product to local retailers at Perlis, Kedah, Pulau Pinang state whereas at Perak are situated at whole area.